Encyclopedia of materials science and technology - Buschow, K. H. J. (Elsevier, 2001)
The study of materials is interdisciplinary in nature and requires knowledge of research in many related fields, such as physics, chemistry, engineering and even biomedical science. Scientists and engineers working with materials increasingly need a medium for gathering relevant information from the growing amount of literature available. The Encyclopedia of Materials: Science and Technology presents around 1,800 articles written by experts in their fields, resulting in a comprehensive coverage of this broad and wide-ranging subject. It is the only encyclopedia available that covers all of materials science and technology, focussing on the following areas: * Functional Phenomena * Structural Phenomena * Fundamental Core Theory * Structural Materials * Polymers and Materials Chemistry * Functional Materials This title is also available online via ScienceDirect - featuring extensive browsing, searching, and internal cross-referencing between articles in the work, plus dynamic linking to journal articles and abstract databases, making navigation flexible and easy. Please contact your librarian for more information about access to these products within your institution.
Volume 11: Indexes (viii, 474 p.).
Keywords: materiály; materiálové inženýrství; materiálové technologie; nauka o materiálu; materials; materials engineering; materials science; encyklopedie; elektronické knihy; encyclopedias; electronic books